2021
DOI: 10.3389/fcvm.2021.751178
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Pelvic Congestion Syndrome: Visual Analog Scale Follow-Up

Abstract: Purpose: To evaluate medium-term clinical outcomes of transcatheter embolization and stenting in women with several pelvic venous disorders responsible for chronic pelvic pain and varicose veins of the lower limbs.Materials and Methods: The study population included 327 consecutively recruited patients referred to the interventional radiology unit from January 2014 to December 2019 due to chronic pelvic congestion (91; 27.83%), lower limb varices (15; 4.59%), or a combination of both the symptoms (221; 67.58%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
0
8
0
5
Order By: Relevance
“…Pain severity will be based on the VAS score [ 35 ]. A VAS is a 100-mm line where “zero” indicates complete painlessness and “10” indicates the most severe pain imaginable.…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…Pain severity will be based on the VAS score [ 35 ]. A VAS is a 100-mm line where “zero” indicates complete painlessness and “10” indicates the most severe pain imaginable.…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…The use of glue in iliac varicose veins and leak points is effective; however, precise control is required. More recently, Onyx, used alone or in combination with sclerosants, has been proven safe and effective [ 15 , 38 , 39 ].…”
Section: Pvd Treatmentmentioning
confidence: 99%
“…In a large series of 520 patients who underwent embolization of the four main ovarian and iliac axes using coils and plugs, De Gregorio et al [ 42 ] reported a decrease in the mean VAS score from 7.63 ± 0.9 to 0.91 ± 1.5 over 5 years. More recently, Senechal et al [ 39 ] followed-up with 327 patients for an average of 39 months after embolization using Onyx and reported an improvement in the mean VAS pain score from 7 ± 2.4 to 1.2 ± 1.9. The clinical success rate was 92%, and the rates of dyspareunia and postcoital pain decreased from 50% to 19% and 69% to 11%, respectively.…”
Section: Pvd Treatmentmentioning
confidence: 99%
“…Another advantage of embolisation is a high effective rate in pain relief and possibility to repeat intervention in case of recurrence of symptoms. Ovarian vein embolization is generally performed under local anaesthesia and patients are usually discharged from the hospital at the same day [18,19]. In case of a patient with severe kidney failure or allergic to iodine-containing contrast, a procedure can also be performed using CO2 as an alternative contrast agent [20].…”
Section: Treatmentmentioning
confidence: 99%